Experience co-creation in financial services: an empirical exploration. Issue 2 (20th April 2015) - Ponsignon, Frederic; Klaus, Philipp; Maull, Roger S.
Abstract : Purpose: – The purpose of this paper is to explore how financial services (FS) organizations manage the customer experience. It aims to establish what practices are used, to articulate the role of the FS context in influencing the choice of practices, and to identify how these practices support experience co-creation from the perspective of the organization. Design/methodology/approach: – The authors adopt a multiple case study approach. In total, 23 cases provide a rich understanding of the phenomenon studied which permits grounding the findings on robust data. Findings: – The authors identify five practices that are consistently used by FS organizations to manage the customer experience. The findings suggest that four industry-specific characteristics affect the choice of these practices. The results also reveal how these practices support the co-creation of the customer experience. Research limitations/implications: – The authors focus on the FS context only, do not examine the impact of the practices on performance, and do not explore experience co-creation from the perspective of the customer. Practical implications: – Adopting these practices can facilitate a more co-created customer experience, which in turn can provide FS organizations with a competitive differentiator. Originality/value: – The paper advances current knowledge by revealing five customer experience management practices that are specific to the FS context. Moreover, this is one of the first studies to explore experience co-creation from the perspective of the organization and to identify ways in which organizations can support customers in co-creating the experiences.